Inhibiting Receptor of Advanced Glycation End Products Attenuates Pressure Overload-Induced Cardiac Dysfunction by Preventing Excessive Autophagy - Gao, Wenbin; Zhou, Zheng; Liang, Birong; Huang, Yusheng; Yang, Zhongqi; Chen, Yang; Zhang, Lu; Yan, Cui; Wang, Jiajia; Lu, Lu; Wen, Zhaorui; Xian, Shaoxiang; et al. (Frontiers in Physiology, 2018)
The receptor for advanced glycation end products (RAGE) is involved in heart failure by mediating diverse pathologic processes, including the promotion of inflammation and autophagy. However, the role of RAGE in pressure overload-induced heart failure is not well understood. We found that stimulation of RAGE triggered the death of neonatal rat ventricular myocytes (NRVMs), while cell death was alleviated by ATG5 knockdown. Using transverse aortic constriction (TAC) in mice as a model of pressure overload-induced heart failure, we demonstrated that RAGE knockout or RAGE blockade attenuated cardiac hypertrophy and fibrosis as well as cardiac dysfunction at 8 weeks after TAC. Importantly, RAGE knockout reversed upregulation of autophagy related proteins (LC3BII/I and Beclin 1) and reduced cardiomyocyte death, indicating that excessive autophagy after TAC was inhibited. Moreover, RAGE knockout or blockade reduced the upregulation of pp65-NFĸB and BNIP3, which mediate autophagy. Taken together, these results suggest that RAGE plays an important role in the progression of heart failure by regulating autophagy. Therefore, inhibition of the RAGE-autophagy axis could be a promising new strategy for treatment of heart failure.